Discurso médico e diagnósticos online - Monteiro, Ana Augusta Filomena (2021)
In the world and especially in Brazil there has been a spectacular increase in online research on health information, especially diagnoses, treatments and medical prognoses. In psychoanalytic clinic it is common to receive people who having collected an online diagnosis, rely on the knowledge gathered from the machine. This dissertation critically discusses the relatively recent phenomenon of research on internet diagnoses, the implications of a diagnosis outside the clinical instance and its consequences on contemporary life. In this work, I place my investigations on the history of the institution of medical diagnosis and its opposition to clinics that have language as their protagonist – the language clinic and psychoanalysis. Emphasis is given to the presentation and exploration of the characteristics of medical discourse, which offer the necessary conditions to feed on-line research platforms. This paper raises the issue of "risk" implied in this research habit, "risk" for the doctor, but also for the user. It points out the ethical problem of the conversion of the user from subject to object/commodity of the Capital